Fecal Microbiota Changes in Patients With Postpartum Depressive Disorder - Zhou, Yumei; Chen, Chen; Yu, Haibo; Yang, Zhuoxin (Frontiers in Cellular and Infection Microbiology, 2020)
Postpartum depression (PPD) is a unique subtype of major depressive disorder and a substantial contributor to maternal morbidity and mortality. However, to date, the pathogenesis of PPD has still remained elusive, and it may associate with genetic and environmental factors. Gut microbiota has already been proved to be associated with depression, however, a limited number of studies have concentrated on PPD. The aim of the present study was to explore the potential correlations between gut microbiota and PPD. In this study, 57 participants were enrolled, in which fecal samples of 28 patients with PPD and 16 healthy controls (HCs) were collected and then analyzed by 16S rRNA gene sequencing. The results showed that diversity and composition of gut microbial communities were partly different between PPD patients and HCs. The relative abundance of Firmicutes phyla was lower in PPD patients. The levels of several predominant genera were significantly different between PPD patients and HCs. Most notably, the PPD patients experienced reduced levels of Faecalibacterium, Phascolarctobacterium, Butyricicoccus and Lachnospiraceae. In addition, a positive correlation was observed between levels of Butyricicoccus and Barnesiellaceae and the severity of depressive symptoms. Various kinds of bacteria, such as genera Coprobacillus and Dehalobacterium, were found to be associated with levels of sex hormones. Most of gut microbiota with significant differences were engaged in butyrate metabolism pathway. This study indicated the correlation between gut microbiota and PPD, and gut microbiota-based biomarkers may be helpful for diagnosis and treatment of PPD patients. However, further studies need to be conducted to clarify the cause-effect relationship between PPD patients and gut microbiota, and highlight the suitability of gut microbiome as a biomarker.